2014
DOI: 10.4489/kjm.2014.42.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Saccharification Capacity, and Toxigenicity Analyses of Fungal Isolates in Nuruk

Abstract: : Nuruk samples collected from various regions in Korea were investigated in terms of fungal contents and diversity. In measurement of colony forming unit (CFU) in Nuruk suspensions on DRBC agar, Nuruk samples MS4, MS8, and MS10 were among the highest fungal density, with 1,278.9±21.6 (×10 ) were among the samples showing the highest fungal density. CFU per 20 mg Nuruk, respectively. The majority of fungal components were yeasts, including Pichia anomala, P. kudriavzevii, Kluyveromyces marxianus, and Saccharom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Kim et al. () determined that A. flavus and A. parasiticus strains isolated from traditional Nuruk were atoxigenic by observing deletions in the AF gene cluster, such as those in afl R, omt A, and norb‐cyp A genes, and by identifying an AF band through TLC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al. () determined that A. flavus and A. parasiticus strains isolated from traditional Nuruk were atoxigenic by observing deletions in the AF gene cluster, such as those in afl R, omt A, and norb‐cyp A genes, and by identifying an AF band through TLC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, various types of yeast, lactic acid bacteria, and aerobic bacteria that cause alcoholic fermentation are present in Nuruk. Some kinds of Nuruk derived microorganisms that were found by Kim et al [14] are shown in Figure 5.…”
Section: Microorganisms In Nurukmentioning
confidence: 99%
“…Therefore, fermentative molds in low pH environment exhibit high liquefaction and glycation Figure 5. The filamentous fungi and yeasts isolated from various Nuruk samples (scale bar = 5 μm) [14].…”
Section: Microorganisms In Nurukmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the strains of Rhizopus oryzae produce carbohydratedigesting enzymes along with organic acids, ethanol and some useful esters, which can be useful in food industries. Aspergillus fumigatus and Paecilomyces variotii is a fast growing microfungi (that can grow efficiently under a variety of environmental conditions), which shows beneficial effects on human health as an emerging agent of opportunistic disease, particularly to boost the immune system (Kim et al, 2014b;Jang et al, 2014). Recently, Kim et al (2019).…”
Section: Microorganisms In Nurukmentioning
confidence: 99%